STRATEGI PEMANFAATAN MEDIA SOSIAL LABEL REKAMAN SUN EATER RECORDS DALAM MELAKUKAN KAMPANYE DIGITAL KARYA MUSIK INDEPENDEN - Muhammad Raihan Alifiardy; Hedi Pudjo Santosa; Agus Naryoso (Interaksi Online, 2023)
Sun Eater Records is a new independent record label that is categorized as one of the record labels that has an important role in the ecosystem of the independent music industry in Jakarta due to its highly adaptive capabilities in managing social media through its content. With the digitization of the music industry, there is intense competition between musicians and indie record labels to dominate the music charts in Indonesia, so Sun Eater Records still has to compete with other independent record labels in terms of maintaining the average number of streams of its music works. As a social media-adaptive record label, Sun Eater Records has carried out various forms of digital campaigns to promote their music. This study aims to describe the social media utilization strategy of record label Sun Eater Records in conducting digital campaigns for independent music works using Anne Gregory's guidelines for campaign planning steps. This research is described based on nine categories, namely Analysis, Goals and Objectives, Target Audience, Message, Strategy, Tactics, Timescales, Resources, and Evaluation. This study uses a qualitative descriptive method with a case study approach. There are three theories that guide this research, namely Integrated Marketing Communication theory, Information Processing Theory, and Uses and Gratification theory. Data collection techniques used were in-depth interviews and literature study. The result of this research is that the strategy applied to the campaign is to carry out the segmenting process and targeting process, as well as ensuring good coordination and integration between all aspects of the company's business. The implementation tactic was to divide the campaign into three types, namely pre-release, D-day release, and post-release, filled with organic campaigns, non-organic campaigns, short campaigns, and side content.